2013
DOI: 10.1155/2013/135698
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction: A Basic Mechanism in Inflammation-Related Non-Communicable Diseases and Therapeutic Opportunities

Abstract: Obesity is not necessarily a predisposing factor for disease. It is the handling of fat and/or excessive energy intake that encompasses the linkage of inflammation, oxidation, and metabolism to the deleterious effects associated with the continuous excess of food ingestion. The roles of cytokines and insulin resistance in excessive energy intake have been studied extensively. Tobacco use and obesity accompanied by an unhealthy diet and physical inactivity are the main factors that underlie noncommunicable dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 122 publications
3
106
0
3
Order By: Relevance
“…It is largely known that reduction of mitochondrial mass contributes to exercise intolerance, inflammation, and degeneration typical of skeletal muscle wasting and atrophy (61)(62)(63). Interestingly we have shown that the failure of mitochondrial biogenesis upon ␣-Syntrophin down-regulation is associated with increased marker of myotube degeneration.…”
Section: Discussionmentioning
confidence: 59%
“…It is largely known that reduction of mitochondrial mass contributes to exercise intolerance, inflammation, and degeneration typical of skeletal muscle wasting and atrophy (61)(62)(63). Interestingly we have shown that the failure of mitochondrial biogenesis upon ␣-Syntrophin down-regulation is associated with increased marker of myotube degeneration.…”
Section: Discussionmentioning
confidence: 59%
“…10 Thyroid steatosis occurs in the context of obesity-induced ER stress and mitochondrial dysfunction. 16,17 A compensatory response to the stress of obesity might contribute to the high prevalence of oncocytic change in patients with a higher BMI. However, our study is limited by the lack of severely obese PTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many articles have been published on this relationship, but systematic reviews are scarce (Labonte et al, 2013) and incomplete. The association between the consumption of dairy products and inflammation in humans, thus merits clarification for the following reasons: (i) milk and dairy products play qualitatively and quantitatively an important role in human nutrition (Haug et al, 2007); (ii) inflammation, in particular low-grade systemic inflammation, has a significant impact on human health and longevity (Candore et al, 2010); (iii) nutrient metabolism and inflammation are mechanistically closely interconnected (Hotamisligil, 2006;Calder et al, 2011;Klop et al, 2012;Calder et al, 2013;Hernandez-Aguilera et al, 2013).…”
Section: Introductionmentioning
confidence: 99%